Gender Differences in Contribution of Smoking, Low Physical Activity, and High BMI to Increased Risk of Early Reoperation After TKA - Gallo, Jiri; Kriegova, Eva; Kudelka, Milos; Lostak, Jiri; Radvansky, Martin (The Journal of arthroplasty, 2020)
BACKGROUND: The reliable preoperative identification of patients at a high risk of early reoperations (<2 years after primary surgery) after total knee arthroplasty (TKA) could lead to adjustments of the surgical procedure and counseling, thus lowering the percentage of revision surgeries. METHODS: The unselected cohort consisted of 1885 patients (695 men and 1190 women) who underwent TKA implantation between September 2010 and April 2017 at a single tertiary orthopedic center. Multivariate patient similarity networks were applied to identify patient groups at a high risk of early reoperations based on 25 preoperative parameters. RESULTS: Early reoperations (109 cases, 5.8%) were less frequent in women (4.4%; median time to reoperation, 2.0 months) than in men (8.2%; 7.5 months), reaching the highest incidence in younger men (10.9%; <66 years). Of the tested preoperative parameters, the risk of reoperation in men was more likely associated with smoking or obesity (body mass index [BMI] > 30). In women, low physical activity and high BMI were the most likely risk factors for early reoperations. Other factors did not affect the risk of early reoperations, including the primary diagnosis, comorbidities, and surgeon-implanting TKA. CONCLUSION: This study demonstrates the effect of smoking, physical activity, and BMI on the risk of early reoperation after TKA, with the different contribution in men/women. Identification of patient subgroups with a higher risk of early revision after TKA is needed for clinical implementation of precision medicine in orthopedics.
Keywords: index tělesné hmotnosti; body mass index; kouření; reoperace; Retrospective Studies; cvičení; totální endoprotéza kolene; mužské pohlaví; Reoperation; Body Mass Index; Arthroplasty, Replacement, Knee; preoperative parameters; Smoking; ženské pohlaví; early reoperation; risk patient subsets; retrospektivní studie; Humans; total knee arthroplasty; Sex Characteristics; Exercise; patient similarity network; pohlavní dimorfismus; Female; lidé; Male